Entomol Ornithol Herpetol 2019
DOI: 10.35248/2161-0983.8.218
|View full text |Cite
|
Sign up to set email alerts
|

The Major Sweet Potato Weevils; Management and Control: A Review

Abstract: Sweet potato is an important food crop, grown commonly in tropical and subtropical regions, but production has been subjected to less research worldwide, compared to the major staple crops. Sweet potato weevils are the major destructive pest causing drastic yield decline and resulting in a decrease in millions of dollar annually. A wide range of management strategies in controlling sweet potato weevils includes; cultural method, chemical method, biological method, Sterile Insect Technique, soil management, Ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Infestation can also occur through planting vines [17]. Application of parathion and chlorpyrifos insecticides have been used in overcoming weevil infestation on sweet potato, however pesticide residues have been reported [20]. Biopesticides such as azadirachtin and spinosad have been evaluated for their efficacy against the sweet potato weevils in the laboratory, but no studies have been reported on field trials [20].…”
Section: Introductionmentioning
confidence: 99%
“…Infestation can also occur through planting vines [17]. Application of parathion and chlorpyrifos insecticides have been used in overcoming weevil infestation on sweet potato, however pesticide residues have been reported [20]. Biopesticides such as azadirachtin and spinosad have been evaluated for their efficacy against the sweet potato weevils in the laboratory, but no studies have been reported on field trials [20].…”
Section: Introductionmentioning
confidence: 99%